Web-based material requisition system in the supply chain of construction businesses - Afolabi Olushola Adedeji; Abraham Yewande S.; Awosika Oluwafikunmi (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In the construction project delivery process, the supply chain of construction businesses can only be efficient and effective based on the prompt availability of building materials. Whereas, the process of requisition for the materials on the construction site, if not handled appropriately, can adversely affect construction performance. Therefore, the study was aimed at developing a web-based material requisition system (W-BMRS) that will make the supply chain on construction sites seamless and more effective. A use case and an activity block diagram provided an understanding of the users and functionalities of the material requisition platform. In addition, using a different user interface and a database system including a programming language to connect them, the study developed a web-based material requisition system for construction firms using the model view controller (MVC) model. The MVC model comprised of using MySQL, HTML, and PHP. The W-BMRS was tested by sending materials requisition through the supply chain of a construction firm. The results were presented via screenshots of the web-based platform. In conclusion, any construction firm can register on the platform and make use of the web-based materials requisition system to maximize productivity and optimize the use of ICT in their materials’ supply chain process.